Rhizobiumacaciae and R. anhuiense are the dominant rhizobial symbionts of Pisum sativum L. from Yunnan-Guizhou Plateau - Zhang, Junjie; Zhao, Zeyang; Feng, Yufeng; Wang, Jingqi; Zong, Xuxiao; Wang, Entao (Frontiers in Microbiology, 2024)
Aiming at investigating the diversity and geographic distribution of pea-nodulating rhizobia in the subtropical region of Yunnan Province from Yunnan-guizhou Plateau, a total of 615 rhizobial isolates were obtained from root-nodules of the trapping plants and characterized genetically and symbiotically. The isolates discriminated into 43 genotypes by PCR-RFLP of IGS DNA. Multiple locus sequence analysis based on 16S rRNA, recA, atpD, dnaK and rpoB genes placed them into eight clusters corresponding to species R. acaciae, R. anhuiense, R. binae, R. bangladeshense, R. hidalgonense and three suspected novel populations of Rhizobium genosp. I ~ III. R.acaciae was the dominant group (52.5%) followed by R. anhuiense (30.7%). The other species were minor groups. Based on nodC phylogeny, all of them were the symbiovar viciae. All the tested strains showed efficient symbiotic N 2 fixation on pea plants, in which WLB27, WCB18 and WNY29 presented the best PGP effects. Some of the tested strains had better IAA production, with WCB18 as the best producer (64.556 mg/L). Their distribution was mainly affected by soil available phosphorus, available potassium, and effective nitrogen. According to the results of symbiotic effect and resistance tests, strains of WLB27, WCB18 and WNY29 were selected as candidates for creating inoculants. This suggests that the pea-nodulating rhizobia in Yunnan Province form a unique community. The results gave some novel information about the diversity, diversification and biogeography of pea-nodulating rhizobia.